Effect of vitamin D supplementation on muscle function and fracture prevention in elderly individuals with osteoporosis - Aguiar, Estêvão de Carvalho; Aguiar, Stephen Carvalho; Rodrigues , Janaina Damascena; Ferreira, Cristiane Martins (Brazilian Journal of Implantology and Health Sciences, 2025)
Introduction: Osteoporosis has represented a growing public health challenge, characterized by decreased bone mineral density and deterioration of bone tissue microarchitecture, resulting in increased skeletal fragility and fracture risk. In parallel, sarcopenia, defined as the loss of muscle mass and function associated with aging, contributed significantly to the incidence of falls, the main trigger for fractures in the elderly. Vitamin D, a steroid hormone, played a crucial role not only in calcium and phosphorus homeostasis, essential for bone mineralization, but also in the regulation of neuromuscular function, through specific receptors present in muscle tissue that influenced strength and balance. Given this scenario, investigation into the effects of vitamin D supplementation has become an area of intense study. Objective: The objective of this systematic review was to analyze and synthesize the scientific evidence on the efficacy of vitamin D supplementation, alone or in combination with calcium, in improving muscle function and preventing fractures in elderly individuals diagnosed with osteoporosis. Methodology: To prepare this review, a systematic search for articles published in the last 10 years was conducted, following the PRISMA checklist guidelines. The databases consulted were PubMed, Scielo and Web of Science. The following health descriptors and their combinations were used: "osteoporosis", "elderly", "vitamin D", "muscle function" and "fractures". The inclusion criteria were: randomized clinical trials, participants aged 65 years or older and diagnosed with osteoporosis. Review studies, studies with participants who had secondary metabolic bone diseases and research that did not evaluate muscle function outcomes or incidence of fractures were excluded. Results: The results found in the analyzed studies indicated that vitamin D supplementation, especially when patients' baseline serum levels were insufficient or deficient, was associated with an improvement in muscle strength and postural balance. It was found that the correction of hypovitaminosis D contributed to a reduction in the risk of falls. Regarding fracture prevention, the evidence was more robust when vitamin D supplementation was combined with adequate calcium intake. This combination demonstrated a more consistent effect in reducing the incidence of nonvertebral and hip fractures in elderly populations, particularly those in institutional care. Conclusion: It was concluded that vitamin D supplementation played a relevant role in improving neuromuscular function in elderly people with osteoporosis, a factor that contributed to the reduction in the risk of falls. For effective fracture prevention, the combination of vitamin D supplementation with calcium proved to be more effective than the isolated administration of vitamin D. Maintaining adequate serum levels of vitamin D, therefore, represented a fundamental and integrated therapeutic strategy in the management of osteoporosis in the elderly.